(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study was conducted to analyse the effects of weight training on selected health related physical fitness variables of school children. Ten weeks, 4 days per week training programme was designed for experimentation. Total 30 male subjects of 14 to 16 years’ age group were selected for experimentation. Selected subjects were divided in two groups i.e. experimental group (n=15) which was given selected weight training protocol for the duration of 10 weeks and control group (n=15) was not provided any training protocol. Health related components including Body Composition I.e. Body Fat %, BMI (Body Mass Index), SMM (Skeletal Muscle Mass), FFM (Fat Free Mass) and TBW (Total Body Water), Flexibility, Muscular Strength and Muscular Endurance i.e. (i) Dynamic Muscular Strength & Muscular Endurance of Arms and Shoulders (ii) Muscular Strength & Endurance of Trunk and Cardiovascular Endurance were selected as dependent variables. The pre and post test data were collected for Body Composition variables using Body Composition Analyser (IB 770), for flexibility using sit and reach test (in cm), Dynamic Muscular Strength and Endurance (Arms and Shoulder) was assessed using Pull Ups (in numbers) and of Trunk using Bent Knee Sit Ups (Number/min). Cardiovascular Endurance was assessed using 12 min run/walk. To check the significant difference between scores of pre and post training, paired t test was used. To analyse the significant difference (if any) between pre weight training & pre control and post weight training and post control independent t test was used. Descriptive statistics including Mean, t-ratio and SD. were computed. Based on the results, it was concluded that weight training has positive impact on the selected health related physical fitness variables i.e. Body Fat %, SMM, FFM, Flexibility, Muscular Strength and Muscular Endurance i.e. (i) Dynamic Muscular Strength & Muscular Endurance (Arms and Shoulders) (ii) Muscular Strength & Endurance of Trunk and Cardiovascular Endurance. No significant changes were observed in BMI and TBW.